Adhesive systems effect over bond strength of resin-infiltrated and de/remineralized enamel [version 1; peer review: 2 approved] - Borges, Alessandra Buhler [UNESP]; Abu Hasna, Amjad [UNESP]; Matuda, Amanda Guedes Nogueira [UNESP]; Lopes, Stephanie Ribeiro [UNESP]; Mafetano, Ana Paula Valente Pinho [UNESP]; Arantes, Aline [UNESP]; Duarte, Angélica Ferreira [UNESP]; Barcellos, Daphne Camara [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Pucci, Cesar Rogério [UNESP] (F1000Research, 2019)
Background: The purpose of this study was to evaluate the effect of different bonding agents on bond-strength to demineralized enamel after remineralizing treatments and resin infiltration. Methods: Buccal enamel of 120 bovine incisors was polished and then were divided into five experimental groups: SE (sound enamel); DE (demineralized enamel); AS (demineralized enamel immersed in artificial saliva for eight weeks); NaF (demineralized enamel treated with 0.05% sodium fluoride solution (one minute) for eight weeks); Ic (demineralized enamel infiltrated with a low-viscosity resin (Icon-DGM). These groups were subdivided according to adhesive system used: Self-etching adhesive Adper Easy One (3M/ESPE) and etch-and-rinse adhesive Single Bond (3M/ESPE). The composite resin blocks were fabricated using a Teflon matrix. A thermomechanical cycling machine was used to carry out the artificial aging of the specimens and thus were sectioned into sticks. The microtensile tests were performed using a universal testing machine at a cross-head speed of 1 mm/min. Data (in MPa) were subjected to two-way ANOVA and Tukey’s tests (5%). Results: Significant differences were found for both factors tested and interactions (p<0.05). Tukey’s test results of µTBS (mean ± SD) were: Etch-and-rinse SE (28.79±3.93); DE (30.41±7.22); AS (29.03±3.33); NaF (29.81±4.06)a; Ic (29.47±5.5);  and self-etching SE (30.37±6.96); DE (14.62±4.47); AS (9.79±2.32); NaF (9.36±2.31); Ic (30.78±8.68). Conclusions: Resin infiltration did not affect the bond strength of demineralized enamel for both adhesive systems tested. For etch-and-rinse adhesive, no differences were observed for the tested groups. For self-etching adhesive, only the resin-infiltrated group showed similar bond strength to sound enamel. Both etch-and-rinse and self-etching adhesive systems can be used in resin-infiltrated enamel, if a composite restoration needs to be further performed. In enamel that has undergone the de/remineralization process, the use of a total-etch adhesive might be preferable for the restorative procedure.
Keywords: Adhesives; Demineralization; Enamel; Remineralization; Resin infiltration